SYSTEMS OF RULES AND THE RISK OF INJURY IN TRADITIONAL TYPES OF BELT-BAR WRESTLING IN THE INTERNATIONAL COMPARATIVE ASPECT (American Journal of Technology and Applied Sciences, 2024)
Traditional belt wrestling forms represent a significant segment of national and international martial arts, in which the rule system plays a key role not only in preserving cultural identity but also in shaping the level of competitive injuries. The purpose of this article is to analyze the impact of rule systems on injury risk in Qazaq. Kuresi compared to other traditional and Olympic wrestling disciplines (Alysh, Kurash, judo, wrestling, Ssireum). Based on an analysis of official international regulations and epidemiological data, it was shown that the dominance of standing wrestling, the focus on a "clean victory" with a throw, and the specific nature of permitted holds create a specific injury profile.